The relationship between reasons for living and suicidal ideation : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Auckland, New Zealand - Jaftha, Bruce Adrian (Massey University, 2022)
Suicide and suicide-related behaviours are widely acknowledged as a major public health issue and the acute nature of suicidal behaviour makes it significant in human consciousness. However, the various causes of suicidal thoughts and behaviour are convoluted and not fully understood. Recommendations stemming from research advocate for a better understanding of the suicidal process, specifically suicidal ideation, as this could enhance efforts in the reduction and impact of suicidal behaviour. Research has shown that Reasons for Living explains variance in suicidal ideation that is not explained by recognised risk factors. The aim of this study was therefore to augment our understanding of suicidal ideation in terms of the extent to which reasons for living predicts suicidal ideation after accounting for specific risk factors: depression, hopelessness, thwarted belongness and perceived burdensomeness. This study also sought to explore the extent to which reasons for living potentially moderates the effects of depression on suicidal ideation. Data was gathered via an anonymous online survey questionnaire in a convenience sample of 577 Australian and New Zealand adults. Hierarchal multiple regression models estimated using ordinary least squares were used to determine whether reasons for living was a significant negative predictor of suicidal ideation, and whether the relationship between depression and suicidal ideation is weaker for people with more reasons for living, while controlling for depression, hopelessness, perceived burdensomeness and thwarted belongingness. Results show that reasons for living is a significant negative predictor of suicidal ideation. The results also show that depression predicts higher suicide ideation, and this effect is moderated by reason for living. Structural Equation Modelling (SEM) was applied, with all study variables treated as latent to allow for the effects of measurement error to be explicitly modelled and accounted for. Results showed that although the SEM model was not considered a good fit to the data, the coefficients across the SEM and OLS techniques were comparable. Both models found reasons for living, depression and perceived burdensomeness to be significant predictors of suicidal ideation. The findings of this research could have meaningful clinical relevance in the assessment and evaluation of suicide risk. Specifically, identifying variations in suicidal ideation via reasons for living could guide clinicians in the application of strategies aimed at suicide prevention.
Keywords: 520302 Clinical psychology